Ablation behavior of high-entropy carbides ceramics (Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C upon exposition to an oxyacetylene torch at 2000 °C. Issue 6 (June 2023) - Ni, Na; Ding, Qi; Shi, Yinchun; Jiang, Juan; Li, Ling; Zhang, Ruiji; Liu, Xuanzhen; Fan, Yuchi
Abstract: The ablation performance of a high-entropy ceramic carbide, (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )C, was performed by oxyacetylene ablation flame, simulating the extreme service environment at 2000 ºC. Phase and microstructure characterization at multi-length scales was carried out. During ablation, a compositionally and microstructurally complex oxidation layer formed on the ablation surface, which consisted of a combination of (Zrx Hf1−x )6 (Nby Ta1−y )2 O17, Ti(Nbx Ta1−x )2 O7, and Tix (Zra Hfb Nbc Ta1−a-b-c )1−x O2 . Based on the microstructure information, the ablation mechanisms were proposed considering the oxidation thermodynamics and kinetics. Comparable rates of O inward diffusion and Ti outward diffusion are suggested, and a particular innermost dense layer composed of isolated (Zrx Hf1−x )6 (Nby Ta1−y )2 O17 grains embedded in a continuous Ti(Nbx Ta1−x )2 O7 matrix is considered to be beneficial for a better ablation resistance.